After-Tax Cost of Leasing. - Mitchell, G. B. (The Accounting Review, 1970)
The article critically analyzes the method for calculating the cost of a lease given by economist Thomas H. Beechy. His method involves finding that rate of discount that would make the present value of the cash flows resulting from the decision to lease equal to the cost of the asset being leased. In other words, this discount rate is an internal rate of return, as such and it suffers from some defects of that concept. The rate of discount is supposed to represent the cost of the lease in a form that is comparable with other forms of financing. But Beechy added a non-cash element into his analysis, resulting in his lease interest rate being analogous to the gross, or before-tax, interest rate on debt. An adjustment to Beechy's rate is required to obtain the rate that is directly comparable with the after-tax cost of debt. A more direct way of calculating the after-tax interest rate implicit in a lease is also given. Beechy's implicit lease interest rate suffers from the defects that multiple solutions may exist, no real solution may exist and each solution is consistent with an assumption that surpluses are reinvested at the internal rate of return, and accordingly, if this assumption is not valid, an improper ranking of mutually exclusive relationships may occur.